Legal analysis of the adoption procedure of constitutional laws in foreign countries (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
The practice of constitutional legislation of different countries shows that for comprehensive and effective regulation of legal interactions in state and society the constitution itself is not enough. In countries such as, for example, Azerbaijan, Spain, Italy, Kyrgyzstan, Poland, Russia, France, Czech Republic, as well as Kazakhstan, there is a particular type of normative legal acts – constitutional laws, which act together with the national Constitution and develop its provisions. In this regard, the article describes the concept and characteristics of the constitutional laws, discusses their views and legal features. It determines the legal nature of the role, place and significance of the constitutional laws in the system of constitutional law sources of foreign countries. A comparative legal research of the procedure of adoption of constitutional laws in foreign countries is conducted and the historical and contemporary conditions for the adoption of the constitutional laws in the constitutional practice of these countries is being studied.